Advantages and pitfalls of machine translation for party research: the translation of party manifestos of European parties using DeepL - Plenter, Johanna Ida (Frontiers in Political Science, 2023)
Parties are the central actors in representative democracies as they perform important democratic functions. Thus, the identification of party positions is a crucial concern. Party researchers mainly rely on party manifestos to estimate policy positions. However, the analysis of manifestos is accompanied by challenges—one of the biggest being cross-national comparisons because of different institutional settings and languages. This article discusses machine translation (MT) as a new option for party research, and reports on the author's experiences with the translation of more than 200 party manifestos using the commercial artificial intelligence (AI) translation tool DeepL. To make this approach widely applicable, the (technical) procedure, including its problems and workarounds for large-scale projects, is presented as a step-by-step guide using R. Additionally, drawing on the most recent German, Estonian, Italian and Polish parliamentary election manifestos this article evaluates the quality of the DeepL translations by applying both back translation and Wordfish analyses. The main findings indicate that DeepL offers high-quality translations as more than 90% of the checked sentences are reproduced word-for-word or at least synonymously and with stable positioning on the left-right scale of both original and English translation. The results have greater implications for political science research as they speak to the reliability of machine translation for political texts.